Insights on the structure and stability of Licanantase: a trimeric acid-stable coiled-coil lipoprotein from Acidithiobacillus thiooxidans - Fernando Abarca; Sebastian E. Gutierrez-Maldonado; Pilar Parada; Patricio Martinez; Alejandro Maass; Tomas Perez-Acle (PeerJ, 2014)
Licanantase (Lic) is the major component of the secretome of Acidithiobacillus thiooxidans when grown in elemental sulphur. When used as an additive, Lic improves copper recovery from bioleaching processes. However, this recovery enhancement is not fully understood. In this context, our aim is to predict the 3D structure of Lic, to shed light on its structure-function relationships. Bioinformatics analyses on the amino acid sequence of Lic showed a great similarity with Lpp, an Escherichia coli Lipoprotein that can form stable trimers in solution. Lic and Lpp share the secretion motif, intracellular processing and alpha helix structure, as well as the distribution of hydrophobic residues in heptads forming a hydrophobic core, typical of coiled-coil structures. Cross-linking experiments showed the presence of Lic trimers, supporting our predictions. Taking the in vitro and in silico evidence as a whole, we propose that the most probable structure for Lic is a trimeric coiled-coil. According to this prediction, a suitable model for Lic was produced using the de novo algorithm “Rosetta Fold-and-Dock”. To assess the structural stability of our model, Molecular Dynamics (MD) and Replica Exchange MD simulations were performed using the structure of Lpp and a 14-alanine Lpp mutant as controls, at both acidic and neutral pH. Our results suggest that Lic was the most stable structure among the studied proteins in both pH conditions. This increased stability can be explained by a higher number of both intermonomer hydrophobic contacts and hydrogen bonds, key elements for the stability of Lic’s secondary and tertiary structure.